2001
DOI: 10.1128/aem.67.1.162-171.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of the DmpR-Mediated Regulatory Circuit in Bacterial Biodegradation Properties in Methylphenol-Amended Soils

Abstract: Pathway substrates and some structural analogues directly activate the regulatory protein DmpR to promote transcription of the dmp operon genes encoding the (methyl)phenol degradative pathway of Pseudomonas sp. strain CF600. While a wide range of phenols can activate DmpR, the location and nature of substituents on the basic phenolic ring can limit the level of activation and thus utilization of some compounds as assessed by growth on plates. Here we address the role of the aromatic effector response of DmpR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 54 publications
2
39
0
Order By: Relevance
“…Alternatively micro-scale niches in the soil environment may be present where the halogenated phenols were reduced sufficiently to enable localized onset of phenol degradation. The soil conditions could possibly also promote rapid adaptation of A. chlorophenolicus to the substrates present as reported previously for another phenol-degrading strain (Sarand et al 2001).…”
Section: Discussionmentioning
confidence: 84%
“…Alternatively micro-scale niches in the soil environment may be present where the halogenated phenols were reduced sufficiently to enable localized onset of phenol degradation. The soil conditions could possibly also promote rapid adaptation of A. chlorophenolicus to the substrates present as reported previously for another phenol-degrading strain (Sarand et al 2001).…”
Section: Discussionmentioning
confidence: 84%
“…Also, the regulators of TOL meta-cleavage pathway genes, XylS and XylS1, differ in only five amino acids but have different effector profiles and display different sigma factor dependence (37). Finally, the ability of bacterial strains to grow with multiple hydroxylated aromatic substrates has been linked to enhanced effector responses, such as those caused by single-amino-acid changes in DmpR, a regulator of phenol degradation genes (40). Therefore, it seems reasonable that the few differences between NtdR and NagR could drastically alter the effector profile as well as the observed basal level of expression.…”
Section: Discussionmentioning
confidence: 99%
“…A plasmid carrying DmpR was introduced into the selection Po-km strain (Po is the promoter activated by DmpR). Further analysis demonstrated that these strains had point mutations within the A domain of DmpR, which produced an enhanced response to 4-methylphenol (Sarand et al, 2001). This produced one mutant bearing a point mutation in the A domain of the protein, which displayed not only a novel response to 4-ethylphenol but also showed an increased reaction to 4-methyphenol and 3,4-dimethyphenol.…”
Section: Sensing Signals With Transcriptional Regulators Of Environmementioning
confidence: 99%